2000
DOI: 10.1006/jcat.1999.2770
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species on Platinum Gauzes during Partial Oxidation of Methane into Synthesis Gas

Abstract: Platinum gauzes have been studied for the partial oxidation of methane in a high-temperature TAP-2 reactor between 800 and 1100 • C. Two different oxidation procedures were used and the oxygen uptake has been measured. Alternating pulse experiments with oxygen and methane with various pulse intervals have revealed mechanistic information about the platinum catalyzed partial oxidation. It has been shown that carbon monoxide and hydrogen can be produced directly from methane and solid oxidized platinum. In the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 19 publications
3
43
1
Order By: Relevance
“…A large peak in the H 2 O profile is consistent with the indirect pathway for the CPOX process, in which complete oxidation of methane on the front of the reactor is followed by reforming reactions [20]. On the other hand, low and near constant concentration of CO 2 along the reactor, is consistent with direct partial oxidation pathway in which partial oxidation products directly form on the front of the reactor [10,21,22]. Linear extrapolation of product selectivity vs. conversion plots to zero methane conversion (figure 4) suggests initial partial oxidation reaction as represented by equation (4).…”
Section: Resultssupporting
confidence: 69%
“…A large peak in the H 2 O profile is consistent with the indirect pathway for the CPOX process, in which complete oxidation of methane on the front of the reactor is followed by reforming reactions [20]. On the other hand, low and near constant concentration of CO 2 along the reactor, is consistent with direct partial oxidation pathway in which partial oxidation products directly form on the front of the reactor [10,21,22]. Linear extrapolation of product selectivity vs. conversion plots to zero methane conversion (figure 4) suggests initial partial oxidation reaction as represented by equation (4).…”
Section: Resultssupporting
confidence: 69%
“…In studies with Pt and Pt/Rh, hydrogen and CO are shown as primary products at short contact times, whereas an influence on mass transport limitation by the variation of the catalyst geometry has been reported [7,39]. Additionally, a direct formation towards syngas has been suggested in a TAP (temporal analysis of products) reactor, different to this study, albeit on platinum catalysts [40]. There, it was also reported that the definition of the reaction products is driven by oxygen adsorbates, showing different regimes depending on the availability of gas phase oxygen.…”
Section: Reaction Zones In Methane Cpoxcontrasting
confidence: 67%
“…Oxygen species dissolved in the bulk of Pt were assumed to be responsible for direct oxidation of methane to carbon dioxide. In general, the ideas about the participation of various oxygen species in different elementary steps of this Pt-catalysed reaction were later confirmed by Fathi et al [11]. In contrast to Mallens et al [10], the latter authors ascribed CO formation to chemisorbed oxygen species formed either via O 2 dissociation or to oxygen atoms diffusing from the bulk of Pt to the surface.…”
Section: Introductionmentioning
confidence: 93%